Az önkormányzati együttműködés zavarai a Szeged Regionális Hulladékgazdálkodási ISPA projekt üzemeltetésének kezdeti szakaszában - Szabó, Ferenc (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
On the basis of a case study I present the experiences of the operation and the typical operational conflicts of the completed Hungarian EU environmental infrastructure development projects, first of all from the aspect of the cooperation of the beneficiary local governments. In the analyzed case - „Szeged Regional Waste Management Program" ISPA project - the legal beneficiary is the municipality of Szeged, but the other 32 municipalities of the region are also interested in the successful implementation of the project and are responsible for the continuous long run operation.